Investigating L2 Students’ Listening Anxiety: A Survey at a Malaysian University - Tahsildar, Mohammad Nasim; Zailin Shah, Yusoff (Universiti Malaysia Pahang, 2014)
Listening anxiety is said to have a direct effect on listeners’ abilities to comprehend what has been said. This is often because listeners are concerned that the message is so complex that they will not be able to understand what they are listening to. In relevance to listening tests, students’ listening anxiety may prove to be a variable that could affect their listening test scores especially for second language (L2) learners. This preliminary study was carried out, as a part of a bigger experimental study to investigate if L2 students experienced listening anxiety. The Foreign Language Learning Survey (FLLAS) (Kim, 2000) was used as the main data collection instrument. The survey comprised of 33 items, which was tested for reliability in this study (Cronbach Alpha α = .928). Eighty-three (n = 83) undergraduate students from one of the universities in Malaysia participated in the survey. The findings of the survey indicated that the students have a rather high level of listening anxiety. This paper elaborates on areas in which students were most anxious about while listening, which may have some implications on the teaching of listening specifically listening comprehension to L2 students.